An internet of software defined cognitive radio ad-hoc networks based on directional antenna for smart environments. (May 2018) - Carie, Anil; Li, Mingchu; Anamalamudi, Satish; Reddy, Prakash; Marapelli, Bhaskar; Dino, Hayat; Khan, Wahab; Jamal, Waseef
Highlights: In opportunistic radio access-based Software defined Cognitive-MAC protocols, Common Control Channel (CCC) plays a significant role in providing node synchronization, legitimate channel access and exchanging cognitive control message. The Directional antenna-based MAC protocol for software defined CR Ad-hoc networks offer great potential to reduce interference, efficiently reuse spatial spectrum, conserve node transmits power consumption, and extend directional communication range. This paper proposes a Directional Antenna Hybrid CCC based CR-MAC protocol for Smart Environments. In addition, the proposed Directional antenna-based Hybrid CCC-CR-MAC protocol has increased link throughput and reduced link delays with minimized node power consumption when compared with Omni-directional antenna-based software defined CR-MAC protocols. The experimental and simulative results reveal that proposed Directional antenna-based Hybrid CCC-CR-MAC protocol has increased link throughput and reduced link delays with minimized node power consumption when compared with Omni-directional antenna-based software defined CR-MAC protocols. Abstract: In opportunistic radio access based Software defined Cognitive-MAC protocols, Common Control Channel (CCC) plays a significant role in providing node synchronization, legitimate channel access and exchanging cognitive control message. State of the art research in existing CR-MAC protocols design CCC in overlay based In-band or out-of-band spectrum with Omni-directional mode of control and data transmission. However, directional antenna based MAC protocol for software defined CR Ad-hoc networks offer great potential to reduce interference, efficiently reuse spatial spectrum, conserve node transmits power consumption, and extend directional communication range. To achieve above-mentioned features, this paper proposes a "Directional antenna Hybrid CCC based CR-MAC protocol for Smart Environments". The present study proposes Directional Hybrid control channel with GPS which is used to exchange cognitive control information whereas directional opportunistic PU free channel is used for application data transmission. Experimental results reveal that proposed Directional antenna based Hybrid CCC-CR-MAC protocol has increased link throughput and reduced link delays with minimized node power consumption when compared with Omni-directional antenna based software defined CR-MAC protocols.